Script's Spot una serie de videos web para conocer todo acerca de escribir guiones - Lopez Ezaine, Carlos Alberto (2020)
“Script’s Spot” is a serie of videos about script’s subjects, which it’s characterized by the union of two formats such as the didactic video and the videoblog. This union is because of the main objectives of the project, which are the entertainment and the learning about script’s subjects. The video is narrated by a character, who is present in all the episodes and, with his personality, give a friendly and funny style to the video. Also, in the videoblog’s part, it narrates the character's life to create empathy with the viewer and, it try to generate a closer relation between the speech and the viewer. ”Script’s Spot” will be publish in YouTube, in a channel with the same name as the serie of videos. This project comes from the importance of the script in the creative process, and also because of the great demand of script and cinema’s subjects are having in different platforms such as YouTube. This serie try to give a better understanding to the viewers about the script’s subjects that are mentioned in the videos, this it’s done in a funny and friendly way.